THE CONCEPT OF SOCIAL CAPITAL IN EMPOWERING MADURA SOCIETY TOWARDS PROSPERITY - Yuriadi; Norsuhaily Abu Bakar (Journal Publicuho, 2023)
Prosperity is the hope and goal of every individual and society throughout the world and the Madurese in particular. With the concept of social capital which consists of the dimensions of network, norms, trust, and mindset, the Madurese people have the awareness to move forward to create collective welfare on the island of Madura. Researchers in this study used qualitative methods. Data was collected using interviews, observation, and documentation. The technique used in the analysis from Cresswell is organizing and preparing data. The results of the study found that, first, the government must provide consistent assistance in obtaining networks. Collaboration and sharing make it easy to prosper. Second, Rules that are made must be clear benchmarks. Regulations must be able to provide guarantees. Regulations can ensure that people get positions according to expertise. Third, Society needs to be positioned as subjects, in order to get freedom. Provide motivation that learning can increase self-esteem. Society needs to get an education. Fourth, the mindset dimension shows that emancipation between men and women must be created. Society needs to be open-minded/flexible with the times. Society needs new thinking as a comparison. Schools and universities must prioritize quality.